2020
DOI: 10.1371/journal.pone.0235363
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of less invasive surfactant administration in clinical practice—Experience of a mid-sized country

Abstract: There are differences in the adoption rates of less invasive surfactant administration (LISA) worldwide. We aimed to describe and analyze the process of LISA introduction at the country level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The data collection period was February 2018–March 2019. The current research is a follow-up of results from this prospective study, the primary findings of which were published elsewhere ( 12 ).…”
Section: Methodsmentioning
confidence: 97%
“…The data collection period was February 2018–March 2019. The current research is a follow-up of results from this prospective study, the primary findings of which were published elsewhere ( 12 ).…”
Section: Methodsmentioning
confidence: 97%
“…Detailed design and the results of the three studies have been reported elsewhere ( 7 9 ). Table 1 summarizes the studies included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The training of the entire team may have led to more confidence in the handling of the necessary devices and an overall gentler initial care of the infants receiving LISA. Recent studies showed that guidelines and training of operators are helpful to implement LISA safely and successfully in daily routine [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%